Nicotine-based Interventions for Adult Smokers with Diabetes: A Systematic Review - Haseen, Farhana; Rahman, Nafis; Hossain, As-Saba; Rana, Sohel; Chowdhury, Asif Moinur; Mahmud, Hasna Heena; Coyle, Joanne; Notley, Sophie; Barnard, Gabriel; McKeganey, Neil (Archives of Clinical and Biomedical Research, 2024)
Purpose: Starting or continuing to smoke after a diagnosis of diabetes is associated with increased health complications, decreased treatment efficacy, and worse survival outcomes. However, the extent and effectiveness of smoking cessation services among patients with diabetes are poorly understood. Nicotine replacement is one of the available interventions to aid smokers in achieving smoking cessation. This systematic review aimed to provide comprehensive evidence on the effects of nicotine-based interventions to support smoking cessation in diabetic patients. Methods: Electronic searches were carried out on the following databases: Medline, Embase, and Cochrane Library up to November 2022. Searches were supplemented by trial registries, references from identified studies, and review articles. Studies were included if nicotine was used to deliver a smoking cessation intervention and if the impact of the interventions was reported for diabetic patients. All articles were independently screened, selected, extracted, and assessed for quality. Narrative data synthesis was conducted due to heterogeneity. Results: Sixteen studies reporting 12 trials met the inclusion criteria, including randomized controlled trials (n=12), one cluster randomized trial, one non-randomized intervention trial, and two before-after design studies. Of the sixteen studies selected, eight studies exclusively assessed diabetic patients, and eight assessed patients with multiple comorbidities, in which diabetic patients were a subgroup of the total sample. Four studies reported interventions with nicotine that increased cessation rates significantly among the intervention group patients compared to the control group at six-month or twelve-month follow-ups. One trial reported a significant reduction in the self-reported number of cigarettes smoked/ day in the intervention group compared to the control. Additionally, there was a trend toward positive changes in levels of biomarkers of glucose control and metabolic outcomes with the use of nicotine-based interventions. Conclusion: Nicotine, with/without behavioral support, appears to increase smoking abstinence in those diagnosed with diabetes without making a significant negative clinical impact. However, data is limited to identifying the optimal form of nicotine or effective intervention for this population. Additionally, there is no evidence of efficacy in smoking cessation interventions with next-generation tobacco harm-reduction products among people with diabetes.